(untitled) (World Bulletin of Public Health, 2023)
The results of anamnestic, conventional clinical laboratory and special examination methods in 40 children with recurrent broncho-obstructive syndrome were studied. The efficacy of Montelukast sodium in bronchial obstruction was determined depending on the severity of clinical and instrumental data